Perlecan is required for the chondrogenic differentiation of synovial mesenchymal cells through regulation of Sox9 gene expression. Issue 4 (15th June 2016) - Sadatsuki, Ryo; Kaneko, Haruka; Kinoshita, Mayuko; Futami, Ippei; Nonaka, Risa; Culley, Kirsty L.; Otero, Miguel; Hada, Shinnosuke; Goldring, Mary B.; Yamada, Yoshihiko; Kaneko, Kazuo; Arikawa‐Hirasawa, Eri; et al.
ABSTRACT: We previously reported that perlecan, a heparan‐sulfate proteoglycan (Hspg2), expressed in the synovium at the cartilage‐synovial junction, is required for osteophyte formation in knee osteoarthritis. To examine the mechanism underlying this process, we examined the role of perlecan in the proliferation and differentiation of synovial mesenchymal cells (SMCs), using a recently established mouse synovial cell culture method. Primary SMCs isolated from Hspg2 −/− ‐Tg (Hspg2 −/− ;Col2a1‐Hspg2 Tg/− ) mice, in which the perlecan‐knockout was rescued from perinatal lethality, lack perlecan. The chondrogenic‐, osteogenic‐, and adipogenic‐potentials were examined in the Hspg2 −/− ‐Tg SMCs compared to the control SMCs prepared from wild‐type Hspg2 +/+ ‐Tg (Hspg2 +/+ ;Col2a1‐Hspg2 Tg/− ) littermates. In a culture condition permitting proliferation, both control and Hspg2 −/− ‐Tg SMCs showed similar rates of proliferation and expression of cell surface markers. However, in micromass cultures, the cartilage matrix production and Sox9 and Col2a1 mRNA levels were significantly reduced in Hspg2 −/− ‐Tg SMCs, compared with control SMCs. The reduced level of Sox9 mRNA was restored by the supplementation with exogenous perlecan protein. There was no difference in osteogenic differentiation between the control and Hspg2 −/− ‐Tg SMCs, as measured by the levels of Runx2 and Col1a1 mRNA. The adipogenic induction and PPARγ mRNA levels were significantly reduced in Hspg2 −/− ‐Tg SMCs compared to control SMCs. The reduction of PPARγ mRNA levels in Hspg2 −/− ‐Tg SMCs was restored by supplementation of perlecan. Perlecan is required for the chondrogenic and adipogenic differentiation from SMCs via its regulation of the Sox9 and PPARγ gene expression, but not for osteogenic differentiation via Runx2. © 2016 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 35:837–846, 2017.